Quality of Cucumbers Commercially Fermented in Calcium Chloride Brine without Sodium Salts - Erin K. McMurtrie; Suzanne D. Johanningsmeier (Journal of Food Quality)
Commercial cucumber fermentation produces large volumes of salty wastewater. This study evaluated the quality of fermented cucumbers produced commercially using an alternative calcium chloride (CaCl2) brining process. Fermentation conducted in calcium brines (0.1 M CaCl2, 6 mM potassium sorbate, equilibrated) with a starter culture was compared to standard industrial fermentation. Production variables included commercial processor (n=6), seasonal variation (June–September, 2 years), vessel size (10,000–40,000 L), cucumber size (2.7–5.1 cm diameter), and bulk storage time (55–280 days). Cucumber mesocarp firmness, color, bloater defects, pH, and organic acids were measured. Complete lactic acid fermentation was achieved, resulting in terminal fermentation pH values of 3.23 ± 0.09 and 3.30 ± 0.12 for CaCl2 and NaCl processes, respectively. On average, CaCl2 brined, fermented cucumbers were 1.8 N less firm, which remained significant in the finished product (P<0.0001). Color differences evidenced by higher hue and lower chroma values (P<0.0269) were consistent with increased photooxidation in CaCl2 brined cucumbers. Commercial implementation of CaCl2 brines for cucumber fermentation in open tanks variably resulted in texture and color defects that can impact product quality. Additional research is needed to understand the atypical softening observed at the commercial scale and identify process controls for quality improvements.